Pelatihan Penulisan Artikel Populer di Media Massa sebagai Alasan Sosial - Virtuous Setyaka; Rahmi Awalina; Eli Ratni (Warta Pengabdian Andalas, 2020)
Social reason means because there are people or society who should benefit from what is done. The knowledge possessed by lecturers or academics must be used for society. One of the ways to make this knowledge accessible to the public is that lecturers or academics must write it down in the mass media. Mass media is a term that began to be used in the 1920s for a type of media designed to reach a very broad community, often shortened to media. An article published in the mass media is usually referred to as a popular article. The problem is that not every lecturer or academician is able to write popular articles to be published in the mass media. That is why training in writing popular articles was necessary and important to be held, including for lecturers or academics at Andalas University, Padang, West Sumatra, Indonesia. The training was attended by 72 registered lecturers from various faculties: Medicine, Pharmacy, Economics, Dentistry, Humanities, Mathematics and Natural Sciences (MIPA), Public Health, Information Technology, Agriculture, Agricultural Technology, Nursing, Social and Political Sciences (ISIP), and Animal Science.